Kolaborasi Guru dan Mahasiswa : Upaya Kampus Mengajar Angkatan 8 dalam Peningkatan Literasi dan Numerasi di SD Negeri 03 Geragahan - Haura Zakiyah Sanur; Faizal Faizal (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study explores efforts to improve literacy and numeracy through collaboration between teachers and students in the Teaching Campus Program at SD Negeri 03 Geragahan. Literacy and numeracy are essential skills in primary education, but many schools in remote areas still face challenges in achieving expected standards. The study aims to identify and evaluate the effectiveness of this program. The research method used is descriptive qualitative with a case study design. Data were collected through observation, interviews, and documentation, and then analyzed using thematic analysis. The results show that the Teaching Campus Program has a significant positive impact on improving students' literacy and numeracy. There was an increase in reading ability, reading comprehension, reading interest, arithmetic ability, understanding of mathematical concepts, and interest in learning mathematics. The implications of this research highlight the importance of support and commitment from all parties involved in the program to ensure its sustainability and success. This research makes a significant contribution to efforts to improve the quality of education in remote areas and can serve as a reference for similar programs in the future.